Kualitas fisik dan sifat organoleptik bakso daging sapi dengan Penambahan tepung oat (avena sativa) - Robi Dianto; Aaf Falahudin; Rachmat Somanjaya Tifani, SP., MP.; Dini Widianingrum (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Beef meatballs using tapioca flour only contain a small amount of protein, fat and fiber in them. The nutrition is very low, only around 0.1% of the daily recommendation. Therefore, there is a need for healthier alternative flour, one of which is oat flour. This research is a diversification of healthy meatball products made from oat flour which contains better nutrition than tapioca flour. The method used was an experimental study with a completely randomized design pattern of three treatments (substitution of tapioca flour with oat flour at 0%; 50% and 100%) which was repeated seven times. The variables observed were chemical quality (air, protein, fat, carbohydrates), physical quality (pH and cooking loss) and organoleptic properties (color, aroma, texture and taste). Data analysis used analysis of variance (ANOVA). If there is a significant difference between treatments, Duncan's further test is carried out. The results showed that the amount of oat flour had a significant effect (P<0.05) on the pH of the meatballs. The amount of oat flour linearly (P<0.05) reduced the level of meatball cooking loss. The organoleptic properties of meatballs with 50% oat flour are more similar to meatballs using 100% oat flour, and have slightly the same level of preference. It can be concluded that oat flour can be used as a substitute for tapioca flour to improve the physical and organoleptic quality of beef balls. Meanwhile, the ideal oat flour substitution rate is as much as 50%.